Penatalaksanaan Senam Hamil untuk Mengurangi Keluhan Low Back Pain - Intan Sari; Fitri Larasati; Serlly Destiana (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Low back pain (LBP) is one of the most common complaints during pregnancy and can significantly affect maternal comfort and daily activities. Postural changes, weight gain, and shifts in the center of gravity are major contributing factors. Since medication use during pregnancy is limited, non-pharmacological interventions such as prenatal exercise offer a safe and effective alternative to reduce pain. The purpose of this community service program is to provide an intervention in the form of a community-based prenatal exercise program tailored to local conditions, involving health cadres, and complemented with education on the benefits of prenatal exercise in reducing lower back pain complaints. This community service program was conducted at Anisa Maternity Clinic, Sembawa District, Banyuasin Regency, South Sumatra, from September 2 to October 2, 2025, involving 35 pregnant women in their second and third trimesters. The activity consisted of three stages: (1) Preparation (coordination, baseline assessment, and module development), (2) Implementation (health education and structured prenatal exercise twice weekly for 4 weeks), and (3) Evaluation (pre–post assessment using VAS/NRS scale and participant satisfaction questionnaire). The results showed an increase in participants’ knowledge about back pain prevention, improved skills in performing correct prenatal exercise movements, and a reduction in average pain intensity by ≥2 points in 68% of participants. Moreover, 85% of participants reported satisfaction with the program and experienced improved daily function. Two partner midwives were successfully trained as facilitators to sustain the program within the community. The community-based prenatal exercise program at Anisa Maternity Clinic proved effective in reducing LBP complaints and enhancing maternal comfort. The involvement of midwives and the provision of educational materials and exercise videos ensure the program’s sustainability for future maternal health promotion activities.     ABSTRAK Nyeri punggung bawah (Low Back Pain/LBP) merupakan salah satu keluhan tersering selama kehamilan yang dapat mengganggu kenyamanan dan aktivitas ibu hamil. Perubahan postur tubuh, peningkatan berat badan, serta pergeseran pusat gravitasi menjadi faktor utama penyebab keluhan ini. Penggunaan obat-obatan terbatas selama kehamilan, sehingga intervensi non-farmakologis seperti senam hamil menjadi alternatif aman dan efektif untuk mengurangi nyeri. Tujuan pengabdian masyarakat ini diperlukan untuk intervensi berupa program senam hamil berbasis komunitas yang disesuaikan dengan kondisi lokal, melibatkan kader kesehatan, serta dilengkapi dengan edukasi tentang manfaat senam hamil untuk mengurangi keluhan nyeri punggung bawah. Kegiatan pengabdian masyarakat ini dilaksanakan di Klinik Bersalin Anisa Sembawa Kabupaten Banyuasin Sumatera Selatan pada tanggal 2 September–2 Oktober 2025 dengan melibatkan 35 ibu hamil trimester II–III. Kegiatan meliputi tiga tahap:(1) persiapan (koordinasi, survei awal, dan penyusunan modul), (2) pelaksanaan (edukasi kesehatan dan senam hamil terstruktur selama 4 minggu, 2 kali per minggu), dan (3) evaluasi  (penilaian pre–post intervensi menggunakan skala VAS/NRS dan kuesioner kepuasan). Hasil kegiatan menunjukkan peningkatan pengetahuan peserta tentang pencegahan nyeri punggung bawah, keterampilan dalam melakukan senam hamil dengan benar, serta penurunan rata-rata intensitas nyeri sebesar ≥2 poin pada 68% peserta. Selain itu, 85% peserta menyatakan puas terhadap kegiatan dan merasa lebih nyaman dalam melakukan aktivitas sehari-hari. Dua bidan mitra juga berhasil dilatih sebagai fasilitator agar program dapat berlanjut di masyarakat. Program senam hamil berbasis masyarakat di Klinik Bersalin Anisa terbukti efektif meningkatkan kenyamanan dan menurunkan keluhan LBP pada ibu hamil. Keterlibatan bidan dan penyediaan modul serta video panduan memungkinkan keberlanjutan program secara mandiri di posyandu dan kelas ibu hamil.